Transdisciplinary research / Mohd Mustaqim Mohd Nordin - Mohd Nordin, Mohd Mustaqim (Faculty of Civil Engineering, 2017)
A comprehensive review on fatigue damage assessment of reinforced concrete (RC) structures with the aid of acoustic emission (AE) technique has been carried out. The reviews were performed on the background, principle, application, monitoring of RC structures, parameter and analysis using AE technique. Fatigue of RC structures, fatigue test configuration, effect of the fatigue amplitude of RC structures and correlation between AE technique and fatigue damage on RC structures have also been critically reviewed. From the review, two gaps were identified. Firstly, AE analyses such as AE parameter analysis, intensity analysis and average frequency versus RA value based on AE signal collected from located event is still limited. Secondly, fatigue test of RC structures based on increasing fatigue amplitude is still limited especially for RC beam specimen.